Parallel tuning of semi-dwarfism via differential splicing of Brachytic1 in commercial maize and smallholder sorghum - Jiao, Shuping (The New phytologist, 2023)
© 2023 Corteva Agriscience. New Phytologist © 2023 New Phytologist Foundation.